DESIRABLE COMPETENCY IN LEARNING MANAGEMENT OF EARLY CHILDHOOD TEACHERS IN SAMUT SAKHON PRIMARY EDUCATION SERVICE AREA OFFICE - Ouamchaeng, Nipaporn; Maharkan, Pattarapon; Sumbandit, Weena (Academic Journal of Thailand National Sports University, 2023)
The purposes of this research were 1) to study desirable competency in learning management of early childhood teachers in the Samut Sakhon Primary Education Service Area Office, and 2) to study the canonical correlation analysis of desirable competency in learning management of early childhood teachers in Samut Sakhon Primary Education Service Area Office. This research was a survey research from collecting 176 sets of questionnaires from 102 schools in Samut Sakhon Province, The results of the study revealed that 1) desirable competency in learning management of early childhood teachers in Samut Sakhon Primary Education Service Area Office, as a whole, was found at the highest level in all 10 Competency ( = 4.525, S.D. = 0.235). The most average value was ethics and the code of ethics of teaching profession competency. ( = 4.659, S.D. = 0.282), classroom management competency was the second ( = 4.625, S.D. = 0.297) and the least average value was self - development competency ( = 4.352, S.D. = 0.400). 2) The canonical correlation of desirable competency in learning management of early childhood teachers in Samut Sakhon Primary Education Service Area Office in all 10 competencies was statistically significant at .01. The most correlation was assessing early childhood development and experiential learning management competency. Research for learner development competency and experiential learning management competency was the second and the least correlation between self - development Competency, ethics, and the code of ethics of teaching profession competency.